2014
DOI: 10.1158/1078-0432.ccr-13-2858
|View full text |Cite
|
Sign up to set email alerts
|

Functional Kinomics Identifies Candidate Therapeutic Targets in Head and Neck Cancer

Abstract: Purpose To identify novel therapeutic drug targets for p53 mutant head and neck squamous cell carcinoma (HNSCC). Experimental Design RNAi kinome viability screens were performed on HNSCC cells including autologous pairs from primary tumor and recurrent/metastatic lesions, and in parallel on murine squamous cell carcinoma (MSCC) cells derived from tumors of inbred mice bearing germline mutations in Trp53, and p53 regulatory genes: Atm, Prkdc, and p19Arf. Cross-species analysis of cell lines stratified by p53 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
87
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 49 publications
8
87
1
Order By: Relevance
“…Recent report has also shown that Wee-1 kinase inhibition with high doses of MK-1775 leads to unscheduled mitotic entry associated with apoptosis in p53 mutant HNSCC cells (35). In our study, neither PARP-1 cleavage nor APO-BrdU tunnel staining was detected in our isogenic cell HNSCC lines with combination therapy, confirming no engagement of apoptosis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent report has also shown that Wee-1 kinase inhibition with high doses of MK-1775 leads to unscheduled mitotic entry associated with apoptosis in p53 mutant HNSCC cells (35). In our study, neither PARP-1 cleavage nor APO-BrdU tunnel staining was detected in our isogenic cell HNSCC lines with combination therapy, confirming no engagement of apoptosis.…”
Section: Discussionmentioning
confidence: 97%
“…Moser and colleagues have recently shown that MK-1775 potentiates cisplatin response in mice bearing mutant p53 HNSCC cells established as subcutaneous flanks; however, they have not examined efficacy of MK-1775 in oral tongue xenografts (35). Ectopic subcutaneous xenograft models have proven less useful for studying therapeutic agents than orthotopic models that recapitulate the tumor microenvironment (30).…”
Section: Discussionmentioning
confidence: 99%
“…132 In particular, WEE1 (a G2-M cell-cycle regulator) can render synthetic lethality in TP53-mutant tumours because cells without functional p53 lack an effective G1 checkpoint and rely heavily on the G2 checkpoint regulators, such as WEE1, resulting in increased sensitivity of TP53-mutant cells to WEE1 inhibitors. Thus, TP53 mutations with functional consequences need to be revisited as prognostic and p redictive b iomarkers in HNSCC.…”
Section: Tp53mentioning
confidence: 99%
“…Therefore, inhibition of the Wee-1 kinase activity can override a G2 cell cycle arrest and/or result in DNA damage by disrupting replication of the genome, leading to premature accumulation of cells with extensive DNA damage in mitosis and subsequent cell death through mitotic catastrophe (13, 14). Recent work with AZD-1775 (formerly known as MK-1775), a specific inhibitor of Wee-1, and siRNA-mediated depletion indicates that Wee-1 inhibition abrogates the G2 checkpoint and selectively sensitizes tumor cells defective of p53 to various DNA-damaging agents, such as gemcitabine, cisplatin, and inhibits tumor growth in in vivo models (15-18). In light of the findings from these preclinical studies, AZD-1775 has entered phase I and II clinical trials as a chemosensitizer in patients with advanced solid tumors and shows good tolerability with minimal collateral cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%